Analisis Faktor-Faktor Yang MempengaruhiPertumbuhan Ekonomi Di Indonesia Tahun 1986-2014 - Arum Diar, Destri Tama; , Dr. Daryono Soebagyo.,MEc (2017)
This study entitled "Analysis of Factors Affecting Economic Growth in Indonesia Year 1986-2014". This study aimed to analyze and determine how much influence inflation, unemployment, and investment to economic growth in Indonesia in 1986-2014. This study uses secondary data in the form of time series data in 1986-2014, which by Gross Domestic Product (GDP) as an indicator of economic growth, inflation, unemployment, and investment. The analytical method used is multiple linear regression or ordinary least squares (OLS). Based on the analysis found that inflation does not affect the economic growth. While unemployment positive and significant effect on economic growth. Similarly, positive and significant investment. Therefore, the government should expand employment and employment so as to reduce unemployment in Indonesia.